2016
DOI: 10.1016/j.neuron.2016.10.063
|View full text |Cite
|
Sign up to set email alerts
|

Acute Fasting Regulates Retrograde Synaptic Enhancement through a 4E-BP-Dependent Mechanism

Abstract: SUMMARY While beneficial effects of fasting on organismal function and health are well appreciated, we know little about the molecular details of how fasting influences synaptic function and plasticity. Our genetic and electrophysiological experiments demonstrate that acute fasting blocks retrograde synaptic enhancement that is normally triggered as a result of reduction in postsynaptic receptor function at the Drosophila larval neuromuscular junction (NMJ). This negative regulation critically depends on trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 38 publications
4
21
0
Order By: Relevance
“…In drosophila, it has been shown that reduction in TOR signalling in muscle fibres is sufficient to compromise synaptic plasticity through retrograde signalling . Interestingly, this TOR/4E‐BP1‐dependent mechanism acts also during short time periods, like starvation . The idea that retrograde signalling affects the stability of the motor neuron is in line with the fact that we observe significant alterations of the motor neuron by electron microscope.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In drosophila, it has been shown that reduction in TOR signalling in muscle fibres is sufficient to compromise synaptic plasticity through retrograde signalling . Interestingly, this TOR/4E‐BP1‐dependent mechanism acts also during short time periods, like starvation . The idea that retrograde signalling affects the stability of the motor neuron is in line with the fact that we observe significant alterations of the motor neuron by electron microscope.…”
Section: Discussionsupporting
confidence: 85%
“…39 Interestingly, this TOR/4E-BP1-dependent mechanism acts also during short time periods, like starvation. 40 The idea that retrograde signalling affects the stability of the motor neuron is in line with the fact that we observe significant alterations of the motor neuron by electron microscope. Multiple factors have been proposed to be secreted by muscle fibres and are important in NMJ maintenance, particularly during stress conditions.…”
Section: Muscle Mtorc1 Signalling Is Required For Neuromuscular Junctsupporting
confidence: 71%
“…Although these perturbations each disrupt receptors and lead to adaptive increases in presynaptic neurotransmitter release, PhTx- and GluRIIA -mediated PHP signaling exhibit important differences. First, some genes have been identified that are only necessary for GluRIIA -dependent PHP expression, while PHP is robustly expressed following acute PhTx application in larvae with mutations in these genes (Frank et al, 2009; Kauwe et al, 2016; Penney et al, 2016; Spring et al, 2016; Tsurudome et al, 2010). In addition, PhTx-induced PHP expression is translation-independent (Frank et al, 2006), while GluRIIA -induced PHP is blocked by inhibitions to postsynaptic translation through loss of the translational regulator Target of Rapamycin ( Tor ) (Kauwe et al, 2016; Penney et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…First, some genes have been identified that are only necessary for GluRIIA -dependent PHP expression, while PHP is robustly expressed following acute PhTx application in larvae with mutations in these genes (Frank et al, 2009; Kauwe et al, 2016; Penney et al, 2016; Spring et al, 2016; Tsurudome et al, 2010). In addition, PhTx-induced PHP expression is translation-independent (Frank et al, 2006), while GluRIIA -induced PHP is blocked by inhibitions to postsynaptic translation through loss of the translational regulator Target of Rapamycin ( Tor ) (Kauwe et al, 2016; Penney et al, 2012). Although several genes and mechanisms necessary for the expression of PHP in the presynaptic neuron have been identified (Dickman and Davis, 2009; Frank, 2013; Kiragasi et al, 2017), far less is known about the mechanistic differences in postsynaptic transduction between PhTx- and GluRIIA -induced PHP signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Denervation‐evoked impairment of muscle function will result in further muscle disuse, which may exacerbate muscle atrophy with age . In support of the abovementioned notion, studies involving Drosophila showed that TOR and 4E‐BP activity in the muscle tissue retrogradely enhanced presynaptic neurotransmitter release at the neuromuscular junction, while in a mouse model, 4EBP‐regulated cap translation promoted synaptic refinement between neurons in the absence of postsynaptic activity . Taken together, these studies showed that the mTOR/AKT pathway plays a role in regulating the neuronal connectivity with muscle fibers, likely through influencing protein synthesis and degradation in the muscle.…”
Section: Discussionmentioning
confidence: 73%